Evaluation of the In Vitro Sensitivity Pattern of Multi-Drug Resistant Gram-Negative Bacilli to Cefepime - N Shayanfar; A Nateghian; S Mortazavi (Tehran University of Medical Sciences, 2007)
Background: Recent increase in resistance among gram-negative bacteria, particularly in referral centers led to difficulties in medical management of severely ill patients all around the world. Given the economic issues, different epidemiologic status and absence of routine system for susceptibility testing in our setting for new antibiotics including 4th generation cephalosporines, it is an urgent need to evaluate their role in our country. Methods: Various multi-drug resistant (resistant to at least two different representatives from the main groups of commonly used antibiotics including third generation cephalosporines, aminoglycosides and new quinolones) gram-negative bacteria were subcultured again on Muller-Hinton agar. Susceptibility testing was done using disk diffusion method with NCCLS criteria and reported according to the predetermined patterns of resistance, types of organs and site of isolation separately. Results: among 96 samples of MDR gram-negative bacteria, Klebsiella spp, Ecoli, Acinetobacter and pseudomonas spp were dominant. Generalized resistance to all groups was the most common pattern of resistance in our samples, in one third of which, there was sensitivity to forth generation cephalosporines. The best observed response was seen among those bacteria with generalized resistance to third generation cephalosporines and partial resistance to new quinolones. Overall, 36% of isolates were sensitive to Cefepime. Urine culture was the most common site of sampling, still the best sensivety results were observed among those isolates from respiratory site. Conclusion: according to our preliminary study, Cefepime might be used in severe infections of gram-negative origin that show generalized resistance to third generation cephalosporines and partial resistance to new quinolones.